Dietary calcium and phosphorous requirements and feed management for nursery pigs - Wu, Fangzhou (Kansas State University, 2019)
The dissertation consisted of 6 chapters involving studies in heavy weight market pig production, dietary Ca and P requirements for nursery pigs, antimicrobial resistance development in finishing pig microbiota, seasonal growth variability in commercial pig production, and leftover feed management in wean-to-finish pig productions. The first chapter presents a thorough review of published studies involving genetic selection, nutritional requirements, health, welfare, and pork quality of finishing pigs with marketing weight greater than 130 kg and assessed future research needs. Chapter 2 describes 2 experiments that evaluated the growth performance and percentage bone ash of early nursery pigs fed various combinations of Ca and P provided by inorganic sources or phytase. Feeding more than 0.90% dietary Ca decreased average daily gain (ADG), average daily feed intake (ADFI), gain:feed ratio (G:F), and percentage bone ash when diets were at or below NRC (2012) requirement for standardized total tract digestible (STTD) P. However, adding inorganic P or phytase to P deficient diets improved pig performance and alleviated the negative impacts of high dietary Ca concentration on growth performance. The experiment presented in chapter 3 characterized the dose-response to increasing digestible P in diets without or with 2,000 units of phytase for 6- to 13-kg pigs. Increasing STTD P from 80 to 140% of NRC (2012) requirement estimates in diets without phytase, and from 100 to 170% of NRC (2012) in diets with phytase, improved ADG, G:F, and percentage of bone ash. Estimated STTD P requirements varied depending on the response criteria and statistical models and ranged from 91 to >140% of NRC (2012) in diets without phytase, and from 116 to >170% of NRC (2012) for diets containing phytase. In addition, phytase exerted an extra-phosphoric effect on promoting pig growth and improved the P dose responses for ADG and G:F. In chapter 4, a study was conducted to determine the effects of tylosin administration route (through feed, drinking water, or intramuscular injection) on the growth performance and the development of antimicrobial resistance in fecal enterococci of finishing pigs. Pigs that received tylosin injection had decreased ADG and G:F compared with control pigs that did not receive any antibiotic treatment, which may be due to a stress response to the handling during injection administration. Moreover, tylosin administration via injection and feed resulted in a higher probability of enterococcal resistance to erythromycin and tylosin compared with drinking water treatment. Chapter 5 presents a retrospective analysis on the seasonal growth patterns of nursery and finishing pigs in 3 commercial production systems located in the Midwest US. Nursery ADG and ADFI expressed prominent seasonal variations and were similar among systems, whereas nursery G:F was not affected by season. Finisher ADG, ADFI, and G:F varied over seasons, but the magnitudes and patterns of change were system dependent. This chapter also presents the concepts underlying the implementation of a multi-level linear mixed model of production records to analyze seasonality and potentially other decision factors in commercial systems. Finally, in chapter 6, 2 experiments were conducted regarding the strategy of managing leftover finisher feed in a wean-to-finish production system. Experiment 1 evaluated the timing (phase) of feeding 2.5 kg/pig of finisher feed in a 5-phase nursery program. All growth responses decreased immediately when the finisher feed was blended into nursery diets; however, pigs greater than 11 kg (phase 3) had improved ability to compensate for the negative effects of finisher feed on overall growth performance. Experiment 2 was then carried out to investigate the maximum amount of finisher feed can be fed to 11-kg pigs. Increasing the finisher feed budget from 0 to 3.75 kg/pig resulted in a linear decrease in ADG and ADFI. However, the economic analysis indicated no change in income-over-feed-cost due to the timing and dose of blending finisher feed into nursery diets.
Keywords: pig; nutrition; production; feed